The Correct Breastfeeding Education on the Knowledge and Behavior of Postpartum Mothers in the NNICU Room - Probowati, Ririn; Nasukha, Wiwik Hidayati; Syarifah, Anis Satus; Ratnawati, Mamik; Prihartanti, Niken Grah (Chakra Brahmanda Lentera Institute, 2024)
Background: In new mothers there is often a failure of administration early in life. The first day of birth becomes a very vulnerable day because breast milk usually has not come out or only slightly confuses the mother and gives drinks other than breast milk. Purpose of the study was to Analysis of the influence of education on the right way of breastfeeding on the knowledge and behavior of breastfeeding postpartum mothers in the NNICU room of RSUD dr. Soedono, East Java Province. Methods: Research design: Pretest-Posttest Experiment Design. Independent variable: proper breastfeeding education: Dependent variable in: knowledge and behavior of postpartum mothers on proper breastfeeding. How to collect data: questionnaires for knowledge of how to breastfeed and observation sheets to measure appropriate breastfeeding behavior. Population: all postpartum mothers whose babies are being treated in the NNICU room in August – October 2023 is 165 people. Sample: a portion of a population of 28 people. Random random sampling technique. Statistical test using Chi Square test technique. Results: The results of the study before education were carried out almost all (82.1%) postpartum mothers had good knowledge and most (67.9%) had proper breastfeeding behavior. After education: all (100%) postpartum mothers have good knowledge and proper breastfeeding behavior. The results of the Chi Square test analysis with α= 0.05 ρ knowledge=0.018 and ρ attitude=0.007 there is an influence of breastfeeding education on knowledge and appropriate breastfeeding behavior in postpartum mothers Conclusion: Breastfeeding education to postpartum mothers using a leaflet containing interesting pictures, carried out at any time before breastfeeding mothers and always practiced directly with the assistance of officers makes it easier for mothers to remember. Direct practice accompanied by officers makes mothers quickly able to breastfeed appropriately.